ANALISIS PENDAPATAN DAN POLA KONSUMSI RUMAHTANGGA PETANI KELAPA DI KECAMATAN PULAU BURUNG KABUPATEN INDRAGIRI HILIR - Pasaribu, Ade Irayanti; Bakce, Djaimi Bakce '; Yusri, Jum’atri ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research are analyze the structure of income, household consumption patterns coconut farmers and the factor that influenced in Pulau Burung Indragiri Hilir Municipality. The analysis of the income structure and logistic regression methods was used to answer this purpose of this research. Based on the result of the analysis of the income structure, the biggest household income of farmers are donated from work income that sourced from coconut farming income. Household consumption patterns of coconut farmers showed that expenditures of food consumption is greater than consumption of the non food. This indicated that the household of coconut farmers in Pulau Burung are not prosperous yet. The dominant factors that affected household consumption patterns of coconut farmers are household income and the length of householder education. The greater the household income of farmers the opportunity proportion of household expenditures for food growers getting smaller. In order to improve the welfare of coconut farmers, it needs to be a concerted effort to increase the income of the household. This can be done by implementing the Government’s policy of stable prices as well as the effort of controlling the price of inputs. Beside that, it needs to be an effort to increase farmers knowledge through training an coaching Keywords: Structure of Income, Consumption Patterns, Welfare.